2014
DOI: 10.1111/zph.12133
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Virological Surveillance of Avian Influenza A Virus H9N2 Subtype in Humans and Poultry in Shanghai, China, Between 2008 and 2010

Abstract: We report the serological evidence of low-pathogenic avian influenza (LPAI) H9N2 infection in an occupational poultry-exposed population and a general population. A serological survey of an occupational poultry-exposed population and a general population was conducted using a haemagglutinin-inhibiting (HI) assay in Shanghai, China, from January 2008 to December 2010. Evidence of higher anti-H9 antibodies was found in serum samples collected from poultry workers. During this period, 239 H9N2 avian influenza vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 56 publications
(66 reference statements)
5
42
1
Order By: Relevance
“…The overall prevalence of AIV subtype H9 was 10.0% (95% CI: 5.61%-14.39%), which fell between the 2.5% prevalence estimates reported from China (6) and that of 16.5% from Bangladesh (7) The highest prevalence was seen in Ravi town (17.1%; 95% CI: 4.5%-29.8%) followed by Data Gunj Bakhsh town (14.3%; 95% CI: 2.5%-26.0%) ( Table Supplementary Appendix …”
mentioning
confidence: 52%
“…The overall prevalence of AIV subtype H9 was 10.0% (95% CI: 5.61%-14.39%), which fell between the 2.5% prevalence estimates reported from China (6) and that of 16.5% from Bangladesh (7) The highest prevalence was seen in Ravi town (17.1%; 95% CI: 4.5%-29.8%) followed by Data Gunj Bakhsh town (14.3%; 95% CI: 2.5%-26.0%) ( Table Supplementary Appendix …”
mentioning
confidence: 52%
“…With a genetically diverse population, LPAI H9N2 viruses have infected both wild and domestic species of birds and mammals (Blair et al, 2013;Peng et al, 2013;Shanmuganatham et al, 2013;Wang et al, 2014;Zhou et al, 2014;Zhu et al, 2013) and have also contributed their six internal gene segments to the H7N9 viruses (Bi et al, 2014;Gao et al, 2013). Thus, there is a great deal of interest in developing vaccines to prevent the transmission and control the ubiquity of H9N2.…”
Section: Introductionmentioning
confidence: 95%
“…During the same period, a newly emergent avian H10N8 virus, also with six H9N2-like internal genes, was reported to cause fatal human infections in China (4). In the meantime, H9N2 viruses continued to cause human infections in China and other countries based on etiological and serological evidence (5)(6)(7)(8)(9)(10)(11)(12). We recently found that avian H9N2 viruses have undergone significant genetic evolution, especially in their internal genes, to form a predominant genotype (G57), which in turn provided the internal genes to multiple new subtypes, including H7N9 and H10N8 viruses (13).…”
mentioning
confidence: 99%